GRICE’S POLITENESS MAXIMS IN JAPANESE BENEFACTIVECAUSATIVE EXPRESSIONS: A STUDY OF PRAGMATICS (MAKSIM KESANTUNAN GRICE DALAM UNGKAPAN BENEFAKTIFKAUSATIF BAHASA JEPANG: KAJIAN PRAGMATIK) - Sri Iriantini (Metalingua: Jurnal Penelitian Bahasa, 2021)
ABSTRACT A culture of a community may be reflected in the way in which language is used. In this sense, a nation with fruitful values of politeness will provide itself with a values-contained language; pertaining to its culture. Japanese, for example, maintains these values, reflecting how its people perceive and act to their world. As a result, Japanese has specific expressions with a subtle moral sense to show addresses a respect, and to humble oneself; described by benefactive-causative structure with verb ‘juju’ or benefactive verbs attached to causative verbs as a case (Juju hojodoushi).  The use of Japanese benefactive-causative expression in a particular conversational situation, is mostly related to the kinship of conversational participants, to the concept of ‘uchi-soto’ (inclusive-exclusive) believed by Japanese community, and to intimate relation of the participants of the utterances. Presenting close relationship, benefactive verbs take a normal form, and subtle ones (taiguukei) will be given to represent unfamiliar relationship.Learning from the phenomena, pragmatic approach may employ to the analysis of the use of Japanese benefactive-causative expression; using context, and others related to utterance situation. In this paper, the present writer focuses on the elements of Grice’s politeness maxims conveyed in Japanese expressions with benefactive-causative verbs.    AbstrakBudaya suatu bangsa dapat tercermin dari bahasa yang digunakan. Sebagai contohnya, Jepang, yang mempunyai budaya sopan santun, dengan menghormati lawan bicara dan merendahkan diri sendiri, yang tercermin dari kesantunan berbahasa ketika bersosialisasi. Salah satunya yaitu penggunaan verba benefaktif yang dilekatkan dengan verba kausatif (jujuhojodoushi), yang berbeda penggunaannya ketika digunakan untuk lingkungan orang lain (bentuk hormat) dan untuk lingkungan sendiri  (bentuk merendahkan diri). Kesantunan dalam ekspresi kausatif benefaktif dalam suatu tuturan ini berkorelasi dengan partisipan dalam tuturan tersebut, konsep ‘uchi (inklusif) - soto (eksklusif)’, dan hubungan kedekatan antara partisipan. Oleh karena itu, penelitian ini akan mengkajinya secara pragmatis, terutama dikaitkan dengan maksim kesopanan dari Grice, penandanya, dan hal-hal yang mempengaruhinya.Metode deskriptif kualitatif digunakan dalam peneltian ini dengan melihat fenomena pragmatis yang ditemukan dalam data ekspresi kausatif benefaktif.